Surgical Outcomes and EEG Prognostic Factors After Stereotactic Laser Amygdalohippocampectomy for Mesial Temporal Lobe Epilepsy - Wu, Shasha; Issa, Naoum P.; Lacy, Maureen; Satzer, David; Rose, Sandra L.; Yang, Carina W.; Collins, John M.; Liu, Xi; Sun, Taixin; Towle, Vernon L.; Nordli, Douglas R.; Warnke, Peter C.; et al. (Frontiers in Neurology, 2021)
Objective: To assess the seizure outcomes of stereotactic laser amygdalohippocampectomy (SLAH) in consecutive patients with mesial temporal lobe epilepsy (mTLE) in a single center and identify scalp EEG and imaging factors in the presurgical evaluation that correlate with post-surgical seizure recurrence. Methods: We retrospectively reviewed the medical and EEG records of 30 patients with drug-resistant mTLE who underwent SLAH and had at least 1 year of follow-up. Surgical outcomes were classified using the Engel scale. Univariate hazard ratios were used to evaluate the risk factors associated with seizure recurrence after SLAH. Results: The overall Engel class I outcome after SLAH was 13/30 (43%), with a mean postoperative follow-up of 48.9 ± 17.6 months. Scalp EEG findings of interictal regional slow activity (IRSA) on the side of surgery (HR = 4.05, p = 0.005) and non-lateralizing or contra-lateralizing seizure onset (HR = 4.31, p = 0.006) were negatively correlated with postsurgical seizure freedom. Scalp EEG with either one of the above features strongly predicted seizure recurrence after surgery (HR = 7.13, p < 0.001) with 100% sensitivity and 71% specificity. Significance: Understanding the factors associated with good or poor surgical outcomes can help choose the best candidates for SLAH. Of the variables assessed, scalp EEG findings were the most clearly associated with seizure outcomes after SLAH.